THE INFLUENCE OF BRAND AMBASSADOR NEO BUDAYA TECHNOLOGY (NCT DREAM) AND PROMOTION ON IMPLUSIVE BUYING ON LEMONILO PRODUCTS - Unsiah Zulfa Ulinnuha; Indah Respati Kusumasari (Universitas KH. Abdul Chalim Mojokerto, 2025)
The Korean Wave phenomenon in Indonesia has significantly influenced consumer behavior, especially among K-Pop fans. This study aims to analyze the influence of Brand Ambassador and Promotion on consumers’ impulsive buying behavior toward Lemonilo products in collaboration with NCT Dream. This associative quantitative research used purposive sampling with 100 respondents who are NCT Dream fans and had previously purchased Lemonilo's special edition products. Data were collected through online questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that both Brand Ambassador and Promotion simultaneously have a significant effect on impulsive buying. Partially, the Brand Ambassador variable shows a dominant influence, supported by indicators such as visibility, credibility, attractiveness, and persuasive power, which are embodied by NCT Dream as public figures. Promotional strategies involving social media, bonus gifts, and digital campaigns also play a role in triggering spontaneous purchasing behavior. These findings confirm that collaboration with popular public figures and creative promotional strategies can effectively increase impulsive buying among millennial and Gen Z markets.